2007
DOI: 10.1128/jb.01808-06
|View full text |Cite
|
Sign up to set email alerts
|

Genome of the Opportunistic Pathogen Streptococcus sanguinis

Abstract: The genome of Streptococcus sanguinis is a circular DNA molecule consisting of 2,388,435 bp and is 177 to 590 kb larger than the other 21 streptococcal genomes that have been sequenced. The G؉C content of the S. sanguinis genome is 43.4%, which is considerably higher than the G؉C contents of other streptococci. The genome encodes 2,274 predicted proteins, 61 tRNAs, and four rRNA operons. A 70-kb region encoding pathways for vitamin B 12 biosynthesis and degradation of ethanolamine and propanediol was apparentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
254
1
11

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 224 publications
(270 citation statements)
references
References 99 publications
(81 reference statements)
4
254
1
11
Order By: Relevance
“…Loss of NrdF expression was confirmed by Western blot (data not shown). As would be expected for a strain whose only remaining RNR is a class III (anaerobic) enzyme (15,43), the mutant could not be propagated in the presence of 6% O 2 , our usual microaerobic growth condition, which is also similar to dissolved O 2 concentrations in venous blood (44). Indeed, this mutant routinely failed to grow in BHI broth under an atmosphere of as little as 1% O 2 (data not shown).…”
Section: Mutagenesis Of S Sanguinis Genes Required Formentioning
confidence: 87%
See 1 more Smart Citation
“…Loss of NrdF expression was confirmed by Western blot (data not shown). As would be expected for a strain whose only remaining RNR is a class III (anaerobic) enzyme (15,43), the mutant could not be propagated in the presence of 6% O 2 , our usual microaerobic growth condition, which is also similar to dissolved O 2 concentrations in venous blood (44). Indeed, this mutant routinely failed to grow in BHI broth under an atmosphere of as little as 1% O 2 (data not shown).…”
Section: Mutagenesis Of S Sanguinis Genes Required Formentioning
confidence: 87%
“…Virtually all bacterial species analyzed to date that possess class Ib RNRs also contain at least one nrdI gene, and in several species, the gene is in the same operon as nrdE and nrdF (14). In SK36, there were three genes annotated as encoding NrdI or NrdI-like proteins, none of which were within or adjacent to the nrdHEKF operon (43). SSA_1668 and SSA_1683 were identified in our previous study as nonessential for growth in 6% O 2 , whereas SSA_2263 was found to be essential (19).…”
Section: Mutagenesis Of S Sanguinis Genes Required Formentioning
confidence: 99%
“…The genome of S. sanguinis SK36 has been sequenced, and nrdH-nrdE-nrdK-nrdF were annotated in a single operon (48). A search for nrdI using B. subtilis nrdI as the query sequence revealed three candidate genes: SSA_2263 (nrdI), SSA_1668 (fmnG), and SSA_1683 (fmnI) (Fig.…”
Section: Identification Of the Genes For Cluster Assembly And Activitmentioning
confidence: 99%
“…The genome sequence of the virulent phage M102, which infects S. mutans, has recently been published (van der Ploeg, 2007). The sequenced genomes of three oral streptococcal strains, including S. gordonii CH1, do not appear to contain prophages (Ajdić et al, 2002;Tanzer et al, 2008;Vickerman et al, 2007;Xu et al, 2007). Temperate phages from Streptococcus mitis, an abundant inhabitant of the oral cavity, have been described (Romero et al, 2004a;Siboo et al, 2003).…”
Section: Introductionmentioning
confidence: 99%